A Needs Analysis of English Learning for Informatics Students In The Digital Era - cahyadi wiharjo (Merwin Publisher, 2025)
This study investigates the English learning needs of Informatics students to support their academic and professional development in the digital era. A mixed-method descriptive survey design was employed to collect data from 120 first- and second-year Informatics students at YPIB University of Majalengka. Data were gathered through questionnaires, semi-structured interviews, and document analysis. The questionnaire demonstrated high reliability, with a Cronbach’s Alpha coefficient of 0.87. The findings reveal that students prioritize reading skills, particularly for understanding programming documentation, technical textbooks, and academic references. Speaking skills, especially for job interviews, workplace communication, and academic presentations, are also perceived as essential for professional readiness. In addition, students heavily rely on English in digital learning environments such as online tutorials, instructional videos, and software documentation. However, major challenges were reported, including limited technical vocabulary and low confidence in speaking English. The study concludes that existing English courses for Informatics students require redesigning to incorporate discipline-specific and digital-era ESP components. These findings not only enrich ESP needs analysis literature in technology-related disciplines but also offer practical guidance for redesigning English curricula responsive to digital-era academic and industry demands